Development and impact of a structured training module for surgical painting and draping among interns - Tharun Ganapathy Chitrambalam; Abinayaah Suresh; Nidhi Mariam George; Sharmila Aristotle (Infection Prevention in Practice)
Summary: Background: Surgical site infections (SSIs) are a global concern affecting patient recovery, prolonging hospital stay and raising healthcare costs. Aim: To address this, a structured training module was implemented to enhance the efficacy of surgical painting and draping among the interns, reducing SSI risk. Methods: A questionnaire was distributed to 194 interns, covering fundamental inquiries on SSIs, aseptic practices and an assessment of the participant's knowledge regarding preoperative skin preparation and draping. Students then attended lectures, demonstrations, hands-on sessions and an operating room workshop dedicated to surgical painting and draping techniques. Proficiency was evaluated through a follow-up questionnaire. Results: There was a significant increase in the percentage of good score from 27.6% to 86.9%. A comparative analysis of surgical site infection (SSI) rates at our institution was performed before and after integrating a cohort of trained clinicians. Conclusion: Although a significant reduction in SSI rates was observed, it cannot be definitively attributed solely to the introduction of the trained personnel. Nonetheless, the findings underscore the potential impact of rigorous training in aseptic techniques on reducing SSI incidence.